P17.17 Anal human papillomavirus (hpv) infection and anal intraepithelial neoplasia (ain) among men who have sex with men (msm) in kuala lumpur, malaysia. (13th September 2015) - Azwa, I; Yee, I; Hairunisa, N; Tan, CH; Harun, S
Abstract : Introduction: MSM in particular HIV positive MSM have an increased risk of anal cancer. There is a paucity of data regarding anal HPV infection and high grade anal intraepithelial neoplasia (HGAIN) among MSM in Malaysia. The study is part of a larger regional collaboration with sites in Bangkok, Bali and Jakarta. The aims of the study were to determine the prevalence, incidence and risk factors associated with high risk anal HPV infection and HGAIN among a cohort of MSM attending a screening site in Kuala Lumpur. Methods: 3 doctors received training in high resolution anoscopy (HRA). 52 MSM participants, 26 HIV positive and 26 HIV Negative, were enrolled into the study. Participants were screened at 3 time points – at baseline, 6 months and 12 months. Each participant completed a questionnaire on demographics, smoking and sexual history. Anal sample collection was then undertaken for liquid based anal cytology and anal HPV genotyping (Linear Array). This was followed by HRA and biopsy of abnormal areas. Patients with AIN 2 or 3 were offered treatment. Each participant was also screened for syphilis (RPR nad TPPA) at each visit. Results: The baseline results are presented. There were no anal cancers. The most common HPV genotype was HPV 16 in 17/52 (33%) participants. 39 (75%) had at least one high risk HPV infection. 26 (50%) had abnormal cytology. 9/52 (17%) had HGAIN (AIN 2 or 3). HGAIN correlated with high grade anal cytology (ASC-H or HSIL) in 6/9 patients. There was 1 newly diagnosed HIV infection. There were 6 incident syphilis infections. Demographic and sexual behaviour data and correlates of HGAIN will be presented. Conclusion: High risk anal HPV infection and HGAIN was highly prevalent at baseline within this cohort of Asian MSM reinforcing the importance of screening within this population. Disclosure of interest: The study was funded by grant from TreatAsia.